first term of an A.P. is a, second term is b and last term is c, then show that sum
of all terms is (a + c)(b +c-2a)
2(b - a) .
Answers
Answered by
23
⏯️⏯️⏯️ANSWER⏮️⏮️⏮️
- difference (d)=b-a
- now ...let the nth term is c......
- therefore......
...
now the sum of n terms
Answered by
7
Step-by-step explanation:
second term = a+d=b
so d=b-a{eq1}
last term =a+ (n-1)d=c
( let d be the common term by which ap increases or decreases and let us assume ap contains n terms)
c=a + (n-1)(b-a){substitute eq1}
→c-a=(n-1)(b-a)
→(c-a)/(b-a)=n-1
→c-a+b-a/b-a=n{ eq2}
sum up to nterms of an ap
=n/2(2a+(n-1)d)
=n/2(a+c)
=(c+b-2a)(a+c)/2(b-a){sub eq2}
Similar questions